Pendekatan Dakwah Masyarakat Orang Asli di Negeri Pahang - Mohd Zin, Ab. Aziz; Mohd Yunus, Ahmad Redzuwan (Jurnal Usuluddin, 2006)
The research is specifically aimed to identify the approach of dawah to Orang Asli community in Pahang. There are two main methods used in this particular research, library research and field research. Meanwhile, the deduction and induction methods are used specifically for data analysis. The finding of the research from various approaches such as through education, welfare, economic and social have been implemented by the Department of Islamic Religious of Pahang, Department of Orang Asli Affairs Pahang, Malaysian Muslim Welfare Organization of Pahang division and the Civilization Development of Asli Community towards the Orang Asli community.